“Free Kurdistan”: Difficult Road to Self-Determination (1970s — XXI Century) - E. G. Vartanyan (Научный диалог)
The period of the struggle of South (Iraqi) Kurdistan for self-determination, namely such events as its transformation into the center of the Kurdish national movement in the Middle East and the proclamation of the Kurdish Autonomous Region (KAR) in 1974 is considered. The creation of a legal precedent, which has acquired an international character, is commented on. The recognition by the Iraqi government of the right of the Kurds to territorial autonomy is assessed as an undoubted success of the national movement of the Kurdish minority. It is noted that the development of the draft of Interim Constitution was preceded by a long discussion between Shiite Arabs, Sunni Arabs and Kurds on the future administrative structure of the country. It is shown that the Baathist regime was not going to solve the Kurdish problem in the country on a truly democratic basis, but only created the appearance of a solution to the issue in order to remove internal and international tensions. The author dwells on the repressive measures of the government of Saddam Hussein against the Kurds. The mass character of repressive measures during the Iranian-Iraqi war of 1980—1988 is emphasized.